STRATEGI PEMBERDAYAAN EKONOMI SANTRI MELALUI BUDIDAYA ENTOK JUMBO UNTUK KETAHANAN PANGAN LOKAL DI PONDOK PESANTREN - Mustakim Mustakim; Gunarti Dwi Lestari; Wiwin Yulianingsih; Rivo Nugroho (IKIP Siliwangi, 2026)
The strategy for empowering the economy of Islamic boarding school students through the cultivation of jumbo Muscovy ducks to fulfill internal needs and as a source of sustainable income for Islamic boarding school students. Qualitative research method using a case study approach, research location at Mamba'ul Ihsan Islamic Boarding School, Ujungpangkah District, Gresik Regency. This research took place from October 2025 to March 2026. The research subjects were 10 informants and the data collection techniques used were participant observation, in-depth interviews, and document studies. Field data analysis used data reduction, data presentation, and conclusion drawing. The validity of research data uses source triangulation, technical triangulation, and time triangulation. The results of the study describe the economic empowerment strategy through jumbo Muscovy duck cultivation in Islamic boarding schools using six stages: program planning, technical training, program implementation, program evaluation, program results and program impacts. The strategy for empowering students' economics equips students with adaptive abilities, improves students' skills, self-confidence, and increases independence based on work experience. The contribution of jumbo Muscovy duck cultivation to local food security makes Islamic boarding schools a means of animal protein food availability, expanding independent and affordable food access, as an innovation in the use of waste for the utilization of alternative feed for jumbo Muscovy ducks, food stability in the Islamic boarding school environment, and as a social contribution in the Islamic boarding school environment and the community.